The distribution of scallop seashell (geloina coaxans) in panipahan village pasir limau kapas district rokan hilir regency riau province - Dedi setiawan; Afrizal Tanjung; Elizal ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
The research was conducted on june 2013 in Panipahan village Pasir Limau Kapasdistrict Rokan Hilir Regency Riau Province. The aim is to find out the distibutionof scallop seashell (Geloina coaxans) by counting its abundance, attendancefrequency, and morisita distribution index. The survey method was used in thisresearch where the location condivided into 3 stations.Panipahan village waters area has muddy sand substrate. Scallop seashell(Geloina coaxans) were found 16 individu at station 1, 2 individu at station 2, and5 individu at station 3. Morisita distribution index showed that the scallop seashell(Geloina coaxans) in this area belonging to clustered category.Keyword : Geloina coaxans, Distibution, Abundance.